2019
DOI: 10.1109/access.2019.2906343
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Infrastructure of Enterprise Architecture and Business Intelligence & Analytics for Knowledge Management in Education

Abstract: Advances in science and technology, the Internet of Things, and the proliferation of mobile apps are critical factors to the current increase in the amount, structure, and size of information that organizations have to store, process, and analyze. Traditional data storages present technical deficiencies when handling huge volumes of data and are not adequate for process modeling and business intelligence; to cope with these deficiencies, new methods and technologies have been developed under the umbrella of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In addition, a case study of experimental design was presented to improve the quality of teaching at a university in Seoul, South Korea. This study quantitatively and qualitatively analyzed the factors affecting the teaching quality of teachers and selected two factors that could be controlled by teachers and three factors that could not be controlled by teachers for analysis, so as to explore the best teaching methods [ 7 9 ]. The results showed that maintaining a close relationship with students at the beginning of the course and holding a bi-monthly learning session were most effective.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a case study of experimental design was presented to improve the quality of teaching at a university in Seoul, South Korea. This study quantitatively and qualitatively analyzed the factors affecting the teaching quality of teachers and selected two factors that could be controlled by teachers and three factors that could not be controlled by teachers for analysis, so as to explore the best teaching methods [ 7 9 ]. The results showed that maintaining a close relationship with students at the beginning of the course and holding a bi-monthly learning session were most effective.…”
Section: Introductionmentioning
confidence: 99%
“…ere are a lot of matters involved in enterprise lean management quality management, such as courses and evaluation index, etc. Association rules can extract valuable knowledge hidden in data, assist educational administrators to make effective decisions, and improve the management level [19][20][21].…”
Section: Quality Evaluation Of Enterprise Lean Managementmentioning
confidence: 99%
“…The perception of the usefulness of KMS, the existence of IT infrastructure, financial support, and proper training in using the system are some of the most important factors to facilitate its adoption among potential users (Oumran et al, 2021). Moscoso-Zea et al (2019) apply KMSs in HEIs, presenting what they described as "a hybrid information infrastructure for business intelligence and analytics". Their goal was to implement a KMS based on educational data warehouses for analytics and data visualization.…”
Section: Knowledge Management In Heismentioning
confidence: 99%